2020
DOI: 10.1111/risa.13494
|View full text |Cite
|
Sign up to set email alerts
|

Toward General Principles for Resilience Engineering

Abstract: Maintaining the performance of infrastructure‐dependent systems in the face of surprises and unknowable risks is a grand challenge. Addressing this issue requires a better understanding of enabling conditions or principles that promote system resilience in a universal way. In this study, a set of such principles is interpreted as a group of interrelated conditions or organizational qualities that, taken together, engender system resilience. The field of resilience engineering identifies basic system or organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 136 publications
0
27
0
Order By: Relevance
“…This result empirically supports the catastrophic effect of the pandemic on the construction industry and substantiates the urgent needs for construction organizations to systematically develop strategies to cope with a crisis of this scale and severity. To this end, construction organizations can learn from the existing knowledge on effective responses to historical disturbances and preparation for future ones (Hollnagel et al 2006;Yu et al 2020).…”
Section: Student T-test Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result empirically supports the catastrophic effect of the pandemic on the construction industry and substantiates the urgent needs for construction organizations to systematically develop strategies to cope with a crisis of this scale and severity. To this end, construction organizations can learn from the existing knowledge on effective responses to historical disturbances and preparation for future ones (Hollnagel et al 2006;Yu et al 2020).…”
Section: Student T-test Resultsmentioning
confidence: 99%
“…lessons can be learned from construction organizations' recovery from prior economic downturns (Hollnagel et al 2006;Yu et al 2020), the authors conducted a systematic literature review on this research stream following the steps suggested by Tranfield et al (2003). The search was carried out in the Scopus and Web of Science databases with keywords that reflect the economic conditions (e.g., "financial crisis," "economic downturn," "recession*," "economic shock," "hostile environment," or "COVID-19") using Boolean operator AND with those that capture the contexts (e.g., "construction industry," "construction firms," "construction business," "construction organization," or "construction sector") and business strategies (e.g., strateg*, respon*, surviv*, OR recov*).…”
Section: Review Methodologymentioning
confidence: 99%
“…This was because Ponce was not in the direct path of the hurricane, and the region was given more financial support from federal agencies such as FEMA [11]. However, with increasing frequency and intensity of climate related hazards, recent disasters have shown the risk of over-reliance on physical systems, as no engineered system is fail-proof [52]. The simulation results obtained in this study reinforce this point, based on empirical data and modeling, that increasing dependency on physical systems decreases the resilience of communities.…”
Section: Discussionmentioning
confidence: 99%
“…Our answer is that the combined use of RFTO and CMLS facilitates the understanding of water resources systems as a complex adaptive system, a view that emphasizes holistic (rather than reductionist) approaches to a problem (Levin 1998, Holland 2006. This is important to design or management of water resources systems because complex adaptive systems thinking in the mental models of key actors involved in decision making is thought to generally reduce the probability of myopic decisions and, thus, unintended consequences in the long run (Biggs et al 2012, Yu et al 2020. RFTO and CMLS help in this regard by forcing analysts to pay attention to slow variables and feedbacks, potential trade-offs in vulnerability stemming from system modifications, and long-term social change arising from social learning and cross-level interactions within a social hierarchy.…”
Section: Discussion: Complementarity Of Rfto and Cmlsmentioning
confidence: 99%